POLC-A: an assessment of POLCA’s authorization element - Thürer, M. (2019)
“This is a pre-print of an article published in Journal of Intelligent Manufacturing. The final authenticated version is available online at Springer http://dx.doi.org/10.1007/s10845-018-1402-2